Menganalisis Kasus Ronald Tannur 2023 Terhadap Hukum dan HAM - Zai, Heni Erlita Sari; Dachi, Claudia Sri Rahayu Pertiwi; Samonaha Hia, Julius Aplikasi; Mardliyah, Ainul; Naibaho, Juan Lastio; Benedick P.S, Henry; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Our purpose in analyzing this case is aligned with the theme of